Pematangan Gonad Ikan Molly (Poecilia sphenops) yang Diberi Pakan Tubifex dengan Frekuensi Berbeda - Nanda Diniarti (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
Nutritional fulfillment in the maturation process of fish gonads is very important to improve the quality of fish seeds. The purpose of this study was to analyze the frequency of feeding dried silk worms on the gonadal maturity rate of molly (Poecilia sphenops). This research was carried out in the Aquaculture Study Program Laboratory, Mataram University, for 60 days from March to April 2022. This study used an experimental method. The research design used was a completely randomized design (CRD) with 4 treatments, namely P1 = using commercial fish feed, P2 = feeding dried silk worms 2 times a week, P3 = feeding dried silk worms as much as 3 times a week, and P4 = feeding dried silkworms 4 times a week. Each treatment was repeated 3 times. The test fish used were 3 months old with a length range of 3 cm. The amount of feed given was 10% of the weight of the biomass of the test fish, and it was fed 3 times a day. The best treatment gave the highest gonad maturity level, with was P4 of 67% fish in level IV of gonad maturity, a gonad maturity index of 4.68%, absolute length growth of 0.69 cm, and weight growth absolute 0.98 g.